Effect Of Organizational Culture And Leadership Style On Employee Performance Of PT. Raya Azura Persada, South Jakarta - Mogi, Agustina; Warasto, Hestu Nugroho; Aesah, Siti (International Journal of Social and Management Studies, 2022)
This study aims to determine the effect of Organizational Culture and Leadership Style on the performance of employees of PT. Raya Azura Persada. This research is a quantitative research and is a population study. The subjects of this study were all office employees with a total of 45 people. Collecting data using a questionnaire that has been tested for validity and reliability, while data analysis is carried out using multiple linear regression analysis. The results showed that the Organizational Culture variable (X1) had an effect on employee performance as indicated by the results of the t-test with a significance of 0.02, which was smaller than 0.05 and tcount which was greater than ttable 3,257 > 2,018. There is no influence of the Leadership Style variable on employee performance as indicated by a significance value greater than 0.05 and tcount which is smaller than ttable 0.350 <2.018 while the Organizational Culture and Leadership Style variables simultaneously affect the Employee Performance of PT. Raya Azura Persada.